Math, asked by TbiaSupreme, 1 year ago

-10b+8, -36,Subtract the given terms.

Answers

Answered by abhi569
8
( - 36 ) - ( - 10b + 8 )


=> - 36 + 10b - 8


=> -36 - 8 + 10b


=> -44 + 10b


=> -2( 22 - 5b )
.
Answered by mysticd
0
Solution :

Given two expressions are ,


First expression = -10b + 8 ,

Second expression = -36

i ) Subtracting second expression

from first expression , we get

-10b + 8 - ( -36 )

= -10b + 8 + 36

= -10b + 44

ii ) Subtracting first expression from

second expression , we get

-36 - ( -10b + 8 )

= -36 + 10b - 8

= 10b - 36 - 8

= 10b - 44

••••
Similar questions